Microalgae carbon fixation integrated with organic matters recycling from soybean wastewater: Effect of pH on the performance of hybrid system. (June 2020) - Song, Chunfeng; Han, Xiaoxuan; Qiu, Yiting; Liu, Zhengzheng; Li, Shuhong; Kitamura, Yutaka
Abstract: Microalgae have been considered as promising alternative for CO2 fixation and wastewater purification. In our previous work, a hybrid microalgae CO2 fixation concept has been put forward, which initially used carbonate solution absorb CO2, and then provided obtained bicarbonate as nutrition for microalgae growth to avoid the challenge of low CO2 solubility and carbon fixation efficiency in the conventional process. In this work, the proposed hybrid system was further intensified via integrating soybean wastewater nutrition removal with bicarbonate-carbon (NH4 HCO3 and KHCO3 ) conversion. The investigation results indicated that the maximum biomass productivity (0.74 g L −1 ) and carbon bioconversion efficiency (46.9%) were achieved in low-NH4 HCO3 concentration system with pH adjusted to 7. pH adjustment of different bicarbonate systems also enhanced total nitrogen (TN), total phosphorus (TP) and chemical oxygen demand (COD) removal efficiency up to 87.5%, 99.5% and 77.6%, respectively. In addition, maximum neutral lipid (14.4 mg L −1 ·d −1 ) and polysaccharide (14.5 mg L −1 ·d −1 ) productivities could be obtained in the KHCO3 systems, while higher crude protein productivity (48.1 mg L −1 ·d −1 ) was yielded in the NH4 HCO3 systems. Graphical abstract: Image 1 Highlights: Wastewater purification and bicarbonate-carbon conversion hybrid system was designed. pH control was carried out to optimize the performance of hybrid system. Algal biomass could be effectively collected via using NH4 HCO3 as bicarbonate. Wastewater purification performance could be enhanced via adding bicarbonate.